Copper chelation and interleukin-6 proinflammatory cytokine effects on expression of different proteins involved in iron metabolism in HepG2 cell line. Issue 1 (December 2017) - Di Bella, Luca; Alampi, Roberto; Biundo, Flavia; Toscano, Giovanni; Felice, Maria
Abstract Background In vertebrates, there is an intimate relationship between copper and iron homeostasis. Copper deficiency, which leads to a defect in ceruloplasmin enzymatic activity, has a strong effect on iron homeostasis resulting in cellular iron retention. Much is known about the mechanisms underlying cellular iron retention under "normal" conditions, however, less is known about the effect of copper deficiency during inflammation. Results We show that copper deficiency and the inflammatory cytokine interleukin-6 have different effects on the expression of proteins involved in iron and copper metabolism such as the soluble and glycosylphosphtidylinositol anchored forms of ceruloplasmin, hepcidin, ferroportin1, transferrin receptor1, divalent metal transporter1 and H-ferritin subunit. We demonstrate, using the human HepG2 cell line, that in addition to ceruloplasmin isoforms, copper deficiency affects other proteins, some posttranslationally and some at the transcriptional level. The addition of interleukin-6, moreover, has different effects on expression of ferroportin1 and ceruloplasmin, in which ferroportin1 is decreased while ceruloplasmin is increased. These effects are stronger when a copper chelating agent and IL-6 are used simultaneously. Conclusions These results suggest that copper chelation has effects not only on ceruloplasmin but also on other proteins involved in iron metabolism, sometimes at the mRNA level and, in inflammatory conditions, the functions of ferroportin and ceruloplasmin may be independent.